2012
DOI: 10.3758/s13423-012-0282-2
|View full text |Cite
|
Sign up to set email alerts
|

Hungry pigeons make suboptimal choices, less hungry pigeons do not

Abstract: Hungry animals will often choose suboptimally by being attracted to reliable signals for food that occur infrequently (they gamble) over less reliable signals for food that occur more often. That is, pigeons prefer an option that 50 % of the time provides them with a reliable signal for the appearance of food but 50 % of the time provides them with a reliable signal for the absence of food (overall 50 % reinforcement) over an alternative that always provides them with a signal for the appearance of food 75 % o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 29 publications
7
40
0
Order By: Relevance
“…There is some evidence that the real or symbolic nature of the rewards can affect decision making (e.g., Lagorio & Madden, 2005). In fact, we recently found that when pigeons performed the pigeon version of this task under lower conditions of motivation (less food deprived), they showed less of a tendency to make suboptimal choices than did more highly motivated pigeons (Laude, Pattison, & Zentall, 2011) with a result similar to that shown by our self-reported gamblers and depleted participants.…”
Section: Discussionsupporting
confidence: 74%
“…There is some evidence that the real or symbolic nature of the rewards can affect decision making (e.g., Lagorio & Madden, 2005). In fact, we recently found that when pigeons performed the pigeon version of this task under lower conditions of motivation (less food deprived), they showed less of a tendency to make suboptimal choices than did more highly motivated pigeons (Laude, Pattison, & Zentall, 2011) with a result similar to that shown by our self-reported gamblers and depleted participants.…”
Section: Discussionsupporting
confidence: 74%
“…If our pigeon model of suboptimal choice is a reasonably good analog of human gambling behavior, the level of pigeons’ food motivation should predict their degree of suboptimal choice. Laude, Pattison, and Zentall (2012) tested this hypothesis and found support for the relationship. They found that pigeons that were minimally food restricted chose optimally, whereas those that were normally food restricted showed the typical suboptimal choice.…”
Section: The Demographics Of Gambling Behaviormentioning
confidence: 98%
“…If the pigeon model of suboptimal choice is an analog of human gambling, then one might expect the level of pigeons' food motivation be associated with their degree of suboptimal choice. Laude et al (2012) found support for the relationship. They found that pigeons that were normally food restricted showed the typical suboptimal choice, whereas those that were minimally food restricted tended to choose optimally.…”
Section: The Relation Between Level Of Food Restriction and Suboptimamentioning
confidence: 75%